2014
DOI: 10.3928/1081597x-20140527-03
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Cross-linking for Treatment of Progressive Keratoconus in Various Age Groups

Abstract: Before CXL, cones of pediatric keratoconic corneas were located more centrally than in the two older age groups. After CXL, pediatric corneas showed more corneal flattening and more corrected distance visual acuity improvement. Pediatric CXL was equally safe compared to adolescent and adult CXL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 27 publications
7
84
1
1
Order By: Relevance
“…Furthermore, Chatzis and Hafezi [45] found that 88% of pediatric keratoconus patients progressed from initial visit. Soeters et al [54] reported keratoconic patients progressing 2.6 D in 7 weeks to 5.0 D over a year. The rapidity in which pediatric corneas evolve suggests that it may be inappropriate to wait for signs of progression as commonly done in adults to offer treatment, but in fact should be offered at diagnosis [1].…”
Section: Difference Between Adult and Pediatric Keratoconusmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Chatzis and Hafezi [45] found that 88% of pediatric keratoconus patients progressed from initial visit. Soeters et al [54] reported keratoconic patients progressing 2.6 D in 7 weeks to 5.0 D over a year. The rapidity in which pediatric corneas evolve suggests that it may be inappropriate to wait for signs of progression as commonly done in adults to offer treatment, but in fact should be offered at diagnosis [1].…”
Section: Difference Between Adult and Pediatric Keratoconusmentioning
confidence: 99%
“…Adult patients who have undergone the procedure have less relapse [4], better functional and morphological results [55] and more sustainable effect over longer follow-up periods [56]. However, Soeters et al [54] did report more corneal flattening and more visual acuity improvement in children compared to adults after cross-linking, while Vinciguerra et al [57] reported better outcomes in adults ages 18–39. Vinciguerra et al [55] also reported that pediatric corneas had faster recovery of central corneal thickness compared to adults suggesting a faster healing process in young eyes.…”
Section: Difference Between Adult and Pediatric Keratoconusmentioning
confidence: 99%
“…138 Meanwhile another study found that patients over 30 did better after cross-linking than other age groups. 149 …”
Section: Optimizing Cross-linking Successmentioning
confidence: 99%
“…For example, age is associated with changes in visual acuity, as pediatric patients show better improvement than older patients in terms of corrected distance visual acuity (CDVA) following CXL [14, 15]. A Snellen CDVA value worse than 20/40 is also correlated with an improvement in visual acuity following CXL [16, 17].…”
Section: Introductionmentioning
confidence: 99%